Exploring price tolerance in online retail: A comparative analysis of price comparison website use and repeat purchases - Jan Berends; Torsten J. Gerpott (Electronic Commerce Research, 2023)
The present empirical study is the first research to examine how the price tolerance of online buyers correlates with price comparison website (PCW) usage and customer relationship status (CRS). Longitudinal sales data of power tools and household appliances in 8,097 transactions from a German online shop and scraped PCW price data over a 6-months period in 2021 are used for the analysis. Consumer demand falls on average by around 80% per less favorable PCW rank. In addition, PCW (new) customers show significantly less price tolerance than organic (existing) customers. A small but significant interaction effect induces that the correlation of CRS and price tolerance is stronger for organic than for PCW customers.
Keywords: 380; Customer relationship; E-commerce; Online retailing; Price comparison websites; Price tolerance; Repeat purchase behavior